Differences in Weight Changes and the Annual Cycle of Male and Female Arctic Ground Squirrels - McLean, Ian G.; Towns, Alison J. (ARCTIC, 1981)
Arctic ground squirrels (Spermophilus parryii) were studied for three summers near Haines Junction, Yukon Territory. Population characteristics and the behaviour of individual animals were monitored throughout the study. Ground squirrels entered hibernation in the order adult females, juvenile females, then males. Males emerged from hibernation before females. Males stored food in the autumn when conditions permitted, whereas females did not. Males emerged from hibernation having lost significantly less weight than females over winter. Males lost weight during the mating period, whereas females did not. These data are interpreted in terms of the mating period which for males lasts for approximately three weeks, whereas for females it lasts for less than a day.Key words: Ground squirrels, male/female differences, weights, annual cycle